The effect of dental caries and restorative biomaterials on IL-1 β and TNF-α levels in the gingival crevicular fluid - Stefanović, Vladimir; Taso, Ervin; Kanjevac, Tatjana; Abazović, Džihan; Rakić, Mia; Petković-Ćurčin, Aleksandra; Acović, Aleksandar; Vojvodić, Danilo (Vojnosanitetski pregled, 2021)
determining caries biomarkers in the saliva and gingival crevicular fluid (GCF) attracts great attention in the current dental research. The concentration of GCF cytokines is illustrative in depicting the processes in tooth structures. Their relevance must be inspected with aspects of tooth position and caries lesion level. Different impacts of dental restoration materials on GCF IL-1β and TNF-α could be used as a parameter for estimating local inflammation. This paper aimed to estimate the concentrations of the proinflammatory cytokines (IL-1β and TNF-a) in the GCF and to correlate them with caries extension, tooth position, and different restorative biomaterials. Methods. GCF samples were collected from 90 periodontally healthy patients demonstrating at least one tooth with proximal caries and one intact tooth, at the baseline, 7 and 30-days post-treatment. The biomarkers’ profile was investigated in relation to different levels of caries extension (superficial, pulpitis, gangrenous, root affection), defect size, and restorative biomaterial. Results. Before therapy, caries level was significantly associated with GCF IL-1β concentration, demonstrating the lowest level in gangrenous (C4) and superficial caries (C2). Thirty days after therapy, root affection (C5) was characterized by the highest IL-1β concentration. Different dental fillings showed various GCF cytokine changes. CPC induced a significant IL-1β increase in more than 70% of treated patients. Caries lesion size was insignificantly associated with GCF levels of these proinflammatory cytokines, where larger defects were followed by an average cytokine increase. Considering the tooth position before therapy, IL-1β had the highest level in GCF samples from caries-affected canines and second molars, while TNF-α showed the highest levels from canines GCF. Dental restoration induced cytokine increase in canines (IL-1β and TNF-α), 1st and 2nd molars GCF (IL-1β). Conclusion. Inflammation intensity of tooth structures was directly reflected in IL-1β and TNF-α concentrations. Dental restoration significantly affects IL-1β and TNF-α levels, depending on the used dental filling-type material. The profile of these cytokines varied in GCF samples of the tooth with different anatomical positions, where canines and molars demonstrated the highest level. An increase of these proinflammatory cytokines in the absence of any symptomatic manifestation of the inflammatory response can be considered as a possible tooth reparation parameter.